FEM Modelling of Dimensional-Resonant Inductors for LLC Converters in MHz Range - Piepenbrock, Till; Schafmeister, Frank; Böcker, Joachim (SPEEDAM 2024; 27th International Symposium on Power Electronics, Electrical Drives, Automation and Motion)

Experimentally Verified 22 kW, 30 kHz LLC Resonant Converter Design with new Control for a 1 MW Cascaded H-Bridge Converter - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (ECCE Europe 2024; IEEE Energy Conversion Congress & Exposition Europe)

Zermelo - Peckhaus, Volker (Neue Deutsche Biographie, Bd. 28: Wettstein - Zwoch)

Leibniz, Gottfried Wilhelm, General Inquiries on the Analysis of Notions and Truths, edited with an English translation by Massimo Mugnai, Oxford University Press: Oxford 2021 (BSHP New Texts in the History of Philosophy) - Peckhaus, Volker (Mathematical Reviews, MR457231)

Studentisches Gesundheitsmanagement in Deutschland - Ausgangspunkte, Entwicklungen und Status quo - Waltert, Carolin; Kämpfe, Astrid; Steinke, Brigitte (Sport, Bewegung und Gesundheit in internationaler Perspektive. Festschrift zur Verabscheidung von Prof. Dr. Hans Peter Brndl-Bredenbeck)

Duale Karrieren: Chronischer Stress und protektive Ressourcen - Längsschnittstudien im Vergleich zweier Verbundsysteme - Breithecker, Jennifer; Kehne, Miriam (Sport, Bewegung und Gesundheit in internationaler Perspektive. Festschrift zur Verabscheidung von Prof. Dr. Hans Peter Brndl-Bredenbeck)

Einfluss von Luftfeuchtigkeit auf die Fließfähigkeit von Polymerpulvern für das selektive Lasersintern (Studienarbeit) - Walljasper, Ben

Entwicklung eines Bildanalyseverfahrens zur Erfassung des dynamischen Fließverhaltens von Schüttgütern - Liu, Diyi

Forschungsstand zu Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland: ein Scoping Review - Noetzel, Ida; Becker, Linda; Gräfin v. Plettenberg, Elisabeth; Kehne, Miriam (Forum Kinder- und Jugendsport)
Die Studienlage zum Thema Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland zeigt sich vielseitig. Das Forschungsfeld ist neben wenigen umfassenden, überregionalen Studien durch kleinere Studien mit spezifischen inhaltlichen Schwerpunkten gekennzeichnet. Das vorliegende Scoping Review zielt darauf ab, die Erkenntnisse des Forschungsfeldes der circa vergangenen 20 Jahre zu systematisieren. Leitend ist die Forschungsfrage „Wie stellt sich der aktuelle Forschungsstand im Feld von Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland dar?“ Auf Basis einer systematischen Literaturrecherche in fünf Datenbanken konnten aus 2365 Publikationen 52 in die Analyse eingeschlossen werden. Überwiegend wurden regionale Querschnittsstudien mit spezifischem Fokus durchgeführt. Die Studien befassen sich zumeist mit den Rahmenbedingungen von Bewegung, Spiel und Sport im Ganztag sowie mit den Charakteristika von Bewegung, Spiel und Sport im Ganztag. Die Analyse verdeutlicht unter anderem den Mangel an längsschnittlichen Studien sowie den Forschungsbedarf im Bereich der Qualität von Bewegung in diesem Setting.
Keywords: Review; Ganztag; Bewegung; Spiel; Sport; Forschungsstand

Natural near field coupled leaky-mode resonant anti-reflection structures: the setae of Cataglyphis bombycina - Schwind, Bertram; Wu, Xia; Tiemann, Michael; Fabritius, Helge-Otto (Frontiers in Physics)
Leaky mode resonances of the setae of Cataglyphis bombycina are found to enhance the thermal emission of the animals by near field coupling to the chitinous exoskeleton. This is remarkable, as the setae are also an adaption to enhance the reflectivity in the visible wavelength range. Both effects are dependent on morphology, dimensions and spatial arrangement. These parameters were experimentally characterized and simulated by finite difference time domain simulations to elucidate the optical impact of the setae in the mid infrared range and the contribution of leaky mode resonances. This mode of action and the setae’s optical properties in the visible range explain evolutionary strains that led to the actual morphology and size of the setae.

ESLM: Improving Entity Summarization by Leveraging Language Models - Firmansyah, Asep Fajar; Moussallem, Diego; Ngomo, Axel-Cyrille Ngonga (The Semantic Web)

The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults - Revheim, Ingrid; Ballance, Simon; Standal, Adelheid Fretland; Rieder, Anne; Dierkes, Jutta; Buyken, Anette; Gilja, Odd Helge; Hausken, Trygve; Rosendahl-Riise, Hanne (Nutrition & Metabolism)
Abstract Background The cereal fibre β-glucan reduces postprandial glycaemia, however, the underlying mechanisms are not fully understood. Thus, the aim of this study was to investigate the acute effect of a β-glucan-enriched oat bread on gastric emptying half-time ( T 1/2 ), gastric emptying lag phase ( T lag ), and gastric emptying rate (GER), and the secretion of glucagon-like peptide-1 (GLP-1) as potential means to influence postprandial glycaemia. Methods A randomised crossover trial was conducted in 22 healthy adults (age 24.6 ± 3.1 years, BMI 23.1 ± 2.7 kg/m 2 ) receiving 25 g available carbohydrates from a β-glucan-enriched oat bread or a control whole-wheat bread at two non-consecutive days. T 1/2 , T lag , and GER were determined based on ultrasound measures of the cross-sectional gastric antrum area in the fasting state and 15, 30, 45, 60, 90, and 120 min postprandially. Capillary glucose, serum insulin, and plasma GLP-1 concentrations were measured at the same time points. Results A biphasic pattern of gastric emptying with a distinct T lag before the commencement of emptying was observed in most subjects for both bread types. While no differences in GER were evident ( p = 0.562), consumption of the oat bread significantly increased T 1/2 by 18 min and T lag by 14 min compared with the whole-wheat bread ( p = 0.005 and p = 0.010, respectively). In addition, the oat bread significantly reduced iAUC 2h for glucose and insulin responses compared with the whole-wheat bread ( p = 0.001 and p < 0.001, respectively). There were no significant differences in GLP-1 response between the two breads ( p = 0.892). Conclusion The increased T 1/2 and T lag could offer a potential mechanism for the observed attenuation of postprandial glycaemia and insulinemia after consumption of the β-glucan-enriched oat bread compared with the whole-wheat bread. Trial registration : The study is registered at clinicaltrails.gov (NCT04571866).

Protein intake and cancer: an umbrella review of systematic reviews for the evidence-based guideline of the German Nutrition Society - Kühn, Tilman; Kalotai, Nicole; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose It has been proposed that a higher habitual protein intake may increase cancer risk, possibly via upregulated insulin-like growth factor signalling. Since a systematic evaluation of human studies on protein intake and cancer risk based on a standardised assessment of systematic reviews (SRs) is lacking, we carried out an umbrella review of SRs on protein intake in relation to risks of different types of cancer. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and cancer risk published before January 22th 2024, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Ten SRs were identified, of which eight included meta-analyses. Higher total protein intake was not associated with risks of breast, prostate, colorectal, ovarian, or pancreatic cancer incidence. The methodological quality of the included SRs ranged from critically low (kidney cancer), low (pancreatic, ovarian and prostate cancer) and moderate (breast and prostate cancer) to high (colorectal cancer). The outcome-specific certainty of the evidence underlying the reported findings on protein intake and cancer risk ranged from very low (pancreatic, ovarian and prostate cancer) to low (colorectal, ovarian, prostate, and breast cancer). Animal and plant protein intakes were not associated with cancer risks either at a low (breast and prostate cancer) or very low (pancreatic and prostate cancer) outcome-specific certainty of the evidence. Overall, the evidence for the lack of an association between protein intake and (i) colorectal cancer risk and (ii) breast cancer risk was rated as possible . By contrast, the evidence underlying the other reported results was rated as insufficient . Conclusion The present findings suggest that higher total protein intake may not be associated with the risk of colorectal and breast cancer, while conclusions on protein intake in relation to risks of other types of cancer are restricted due to insufficient evidence.

Dietary protein and blood pressure: an umbrella review of systematic reviews and evaluation of the evidence - Boeing, Heiner; Amini, Anna M.; Haardt, Julia; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Introduction This umbrella review aimed to investigate the evidence of an effect of dietary intake of total protein, animal and plant protein on blood pressure (BP), and hypertension (PROSPERO: CRD42018082395). Methods PubMed, Embase and Cochrane Database were systematically searched for systematic reviews (SRs) of prospective studies with or without meta-analysis published between 05/2007 and 10/2022. The methodological quality and outcome-specific certainty of evidence were assessed by the AMSTAR 2 and NutriGrade tools, followed by an assessment of the overall certainty of evidence. SRs investigating specific protein sources are described in this review, but not included in the assessment of the overall certainty of evidence. Results Sixteen SRs were considered eligible for the umbrella review. Ten of the SRs investigated total protein intake, six animal protein, six plant protein and four animal vs. plant protein. The majority of the SRs reported no associations or effects of total, animal and plant protein on BP (all “possible” evidence), whereby the uncertainty regarding the effects on BP was particularly high for plant protein. Two SRs addressing milk-derived protein showed a reduction in BP; in contrast, SRs investigating soy protein found no effect on BP. The outcome-specific certainty of evidence of the SRs was mostly rated as low. Discussion/conclusion This umbrella review showed uncertainties whether there are any effects on BP from the intake of total protein, or animal or plant proteins, specifically. Based on data from two SRs with milk protein, it cannot be excluded that certain types of protein could favourably influence BP.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Nutri-Score 2023 update - Merz, Benedikt; Temme, Elisabeth; Alexiou, Hélène; Beulens, Joline Wilhelma Johanna; Buyken, Anette; Bohn, Torsten; Ducrot, Pauline; Falquet, Marie-Noëlle; Solano, Marta García; Haidar, Hanna; Infanger, Esther; Kühnelt, Charlotte; et al. (Nature Food)

“It’s like I got a new pair of glasses”: Reflections on sense of self, home, and belonging among transnational students in short-term study abroad programs - Müller, Mareike (Study Abroad Research in Second Language Acquisition and International Education)
This study focuses on a specific group of sojourners that has thus far remained rather unexplored in the context of study-abroad research, namely, students with extensive prior experiences of living in, traveling to, and/or familial ties with target-language mediated communities. To this end, this study examines data obtained through episodic interviews with three American students, who grew up in close contact with German-speaking communities and studied abroad in Austria for four weeks. By means of thematic analysis, the pre-study abroad sojourn motives and reflections on sense of self, home, and belonging are contrasted with these students’ immediate and delayed post-study abroad accounts. The results shed light on both the challenges young adults grapple with due to their international biographies and the transformative effects students attribute to their short-term sojourns with regard to redefining who they are and what meaning different places of home and heritage have within their individual trajectories.

Security Analysis of BigBlueButton and eduMEET - Heitmann, Nico; Siewert, Hendrik; Moog, Sven; Somorovsky, Juraj (Applied Cryptography and Network Security)
Video conferencing systems have become an indispensable part of our world. Using video conferencing systems implies the expectation that online meetings run as smoothly as in-person meetings. Thus, online meetings need to be just as secure and private as in-person meetings, which are secured against disruptive factors and unauthorized persons by physical access control mechanisms. To show the security dangers of conferencing systems and raise general awareness when using these technologies, we analyze the security of two widely used research and education open-source video conferencing systems: BigBlueButton and eduMEET. Because both systems are very different, we analyzed their architectures, considering the respective components with their main tasks, features, and user roles. In the following systematic security analyses, we found 50 vulnerabilities. These include broken access control, NoSQL injection, and denial of service (DoS). The vulnerabilities have root causes of different natures. While BigBlueButton has a lot of complexity due to many components, eduMEET, which is relatively young, focuses more on features than security. The sheer amount of results and the lack of prior work indicate a research gap that needs to be closed since video conferencing systems continue to play a significant role in research, education, and everyday life.

Wirtschafts- und Finanzpolitik als Schlüsselbereiche europäischer Einigung - Schönhärl, Korinna; Leucht, Brigitte (Europäische Einigung zwischen Anspruch und Wirklichkeit. Eine historische Bestandsaufnahme)
Im Gespräch loten Brigitte Leucht und Korinna Schönhärl aus, welche Rolle wirtschafts- und finanzpolitische Überlegungen und Faktoren für den europäischen Einigungsprozess gespielt haben und immer noch spielen.
Keywords: Wirtschaftsgeschichte; Europäische Geschichte; Europäische Einigung; Staatsverschuldung; Moderne griechische Geschichte

Green Multi-Objective Scheduling - A memetic NSGA-III for flexible production with real-time energy cost and emissions - Burmeister, Sascha Christian

Histories of Tax Evasion, Avoidance and Resistance - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea
Tax evasion, tax avoidance and tax resistance are widespread phenomena in political, economic, social and fiscal history from antiquity through medieval, early modern and modern times. Histories of Tax Evasion, Avoidance and Resistance shows how different groups and individuals around the globe have succeeded or failed in not paying their due taxes, whether in kind or in cash, on their properties or on their crops. It analyses how, throughout history, wealthy and poor taxpayers have tried to avoid or reduce their tax burden by negotiating with tax authorities, through practices of legal or illegal tax evasion, by filing lawsuits, seeking armed resistance or by migration, and how state authorities have dealt with such acts of claim making, defiance, open resistance or elusion. It fills an important research gap in tax history, addressing questions of tax morale and fairness, and how social and political inequality was negotiated through taxation. It gives rich insights into the development of citizen-state relationships throughout the course of history. The book comprises case studies from Ancient Athens, Roman Egypt, Medieval Europe, Early Modern Mexico, the Ottoman Empire, Nigeria under British colonial rule, the United Kingdom of the early 20th century, Greece during the Second World War, as well as West Germany, Switzerland, Sweden and the United States in the 20th century, including transnational entanglements in the world of late-modern offshore finance and taxation. The authors are experts in fiscal, economic, financial, legal, social and/or cultural history. The book is intended for students, researchers and scholars of economic and financial history, social and world history and political economy. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Share Alike 4.0 license.
Keywords: Tax History; Financial History

The Ability and Intention of Not Paying Taxes in History. Some Introductory Observations - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea (Histories of Tax Evasion, Avoidance and Resistance)
Jean Bodin's list on how the absolutist monarchical state could raise its revenue ranked taxation only in seventh place. From a modern legal perspective, taxes are compulsory transfers of resources that households and enterprises pay to one or several government bodies without receiving an individual, specific benefit in return. Historians have dealt with not paying taxes in various contexts, such as analysing tax resistance and tax resistance movements in history. Tax law is best understood as an outcome of long-term, often conflictual, negotiations and as an expression of specific political mentalities and ideologies. As a consequence, tax law and sometimes even the tax juridical system have a strongly politicised character. Loopholes in tax legislation that enable or facilitate avoidance or evasion can thus be regarded as a result of the interest-driven politics of parliamentary majorities, as the success of concerted lobby pressure.

How to Create a Taxpaying Spirit. A Transnational Examination of an US American and a Western German Tax Education Film in and after World War II - Schönhärl, Korinna (Histories of Tax Evasion, Avoidance and Resistance)
As a case study, this chapter examines two tax education films that were produced 11 years apart in the USA and Western Germany during and after World War II: “The New Spirit” and “Putzke wants to know”. In contrast to America's most popular cartoon character 11 years earlier, Erwin Putzke is in a terrible mood at the beginning of the short film “Putzke wants to know”. The family father and electrician with a workshop of his own is annoyed and upset by the duty of filling in his tax return, grumbling at his wife and daughter and even at their budgie. The film's tax morale message is conveyed to its audience against the backdrop of a sober post-war reality characterised by allied occupation and the Allies' say in West German tax policies during a period of laborious economic build-up after a lost war.

Bibliotheken des Hellwegraums als Orte frühneuzeitlichen Kulturtransfers. Aufriß und Forschungsprogramm - Süßmann, Johannes (Bücher in Westfalen – Westfalen und ihre Bücher. Festschrift für Hermann-Josef Schmalor zum 70. Geburtstag)

UpCy: Safely Updating Outdated Dependencies - Dann, Andreas Peter; Hermann, Ben; Bodden, Eric

Antonia Villinger: Dramen der Schwangerschaft. Friedrich Hebbels „Judith“, „Maria Magdalena“ und „Genoveva“. Baden-Baden: Ergon 2021 - Famula, Marta (Jahrbuch Forum Vormärz Forschung 2022. [in Vorbereitung])

On the Universal Transformation of Data-Driven Models to Control Systems - Peitz, Sebastian; Bieker, Katharina (Automatica)
As in almost every other branch of science, the major advances in data science and machine learning have also resulted in significant improvements regarding the modeling and simulation of nonlinear dynamical systems. It is nowadays possible to make accurate medium to long-term predictions of highly complex systems such as the weather, the dynamics within a nuclear fusion reactor, of disease models or the stock market in a very efficient manner. In many cases, predictive methods are advertised to ultimately be useful for control, as the control of high-dimensional nonlinear systems is an engineering grand challenge with huge potential in areas such as clean and efficient energy production, or the development of advanced medical devices. However, the question of how to use a predictive model for control is often left unanswered due to the associated challenges, namely a significantly higher system complexity, the requirement of much larger data sets and an increased and often problem-specific modeling effort. To solve these issues, we present a universal framework (which we call QuaSiModO: Quantization-Simulation-Modeling-Optimization) to transform arbitrary predictive models into control systems and use them for feedback control. The advantages of our approach are a linear increase in data requirements with respect to the control dimension, performance guarantees that rely exclusively on the accuracy of the predictive model, and only little prior knowledge requirements in control theory to solve complex control problems. In particular the latter point is of key importance to enable a large number of researchers and practitioners to exploit the ever increasing capabilities of predictive models for control in a straight-forward and systematic fashion.

Dimensioning and Lifetime Prediction Model for a Hybrid, Hydrogen-Based Household PV Energy System Using Matlab/Simulink - Möller, Marius Claus; Krauter, Stefan (Solar)
This paper presents a model of an energy system for a private household extended by a lifetime prognosis. The energy system was designed for fully covering the year-round energy demand of a private household on the basis of electricity generated by a photovoltaic (PV) system, using a hybrid energy storage system consisting of a hydrogen unit and a lithium-ion battery. Hydrogen is produced with a Proton Exchange Membrane (PEM) electrolyser by PV surplus during the summer months and then stored in a hydrogen tank. Mainly during winter, in terms of lack of PV energy, the hydrogen is converted back into electricity and heat by a fuel cell. The model was created in Matlab/Simulink and is based on real input data. Heat demand was also taken into account and is covered by a heat pump. The simulation period is a full year to account for the seasonality of energy production and demand. Due to high initial costs, the longevity of such an energy system is of vital interest. Therefore, this model was extended by a lifetime prediction in order to optimize the dimensioning with the aim of lifetime extension of a hydrogen-based energy system. Lifetime influencing factors were identified on the basis of a literature review and were integrated in the model. An extensive parameter study was performed to evaluate different dimensionings regarding the energy balance and the lifetime of the three components, electrolyser, fuel cell and lithium-ion battery. The results demonstrate the benefits of a holistic modelling approach and enable a design optimization regarding the use of resources, lifetime and self-sufficiency of the system

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers - Büchel, Daniel; Torvik, Per Øyvind; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik (European Economic Review)
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England, and several countries in Continental Europe, we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance for cognitive functioning of maintaining good physical health in old age.

Stimuli‐accelerated polymeric drug delivery systems - Rust, Tarik; Jung, Dimitri; Langer, Klaus; Kuckling, Dirk (Polymer International)
The controlled delivery of active pharmaceutical ingredients to the site of disease represents a major challenge in drug therapy. Particularly when drugs have to be transported across biological barriers, suitable drug delivery systems are of importance. In recent years responsive delivery systems have been developed which enable a controlled drug release depending on internal or external stimuli such as changes in pH, redox environment or light and temperature. In some studies delivery systems with reactivity against two different stimuli were established either to enhance the response by synergies of the stimuli or to broaden the window of possible trigger events. In the present review numerous exciting developments of pH-, light- and redox-cleavable polymers suitable for the preparation of smart delivery systems are described. The review discusses the different stimuli that can be used for a controlled drug release of polymer-based delivery systems. It puts a focus on the different polymers described for the preparation of stimuli-sensitive systems, their preparation techniques as well as their stimuli-responsive degradation. © 2022 The Authors. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Industrial Chemistry.
Keywords: drug delivery system; stimuli; polymer; cleavable

Zu unangenehm, zu viel Aufwand oder keine Möglichkeit? – Emotionen und Bereitschaft von Lehramtsstudierenden zur Videografie eigenen Unterrichts - Vogelsang, Christoph; Pollmeier, Pascal; Gockeln, Theresa; Rogge, Tim (Zeitschrift für Bildungsforschung)
Videografien eigenen Unterrichts sind ein mögliches methodisches Werkzeug zur Förderung der professionellen Kompetenz angehender Lehrkräfte, das allerdings innerhalb der Lehramtsausbildung noch nicht breit implementiert ist. Ein möglicher Grund hierfür könnte neben organisatorischen Herausforderungen auch in einer geringen Akzeptanz von Eigenvideografien durch Lehramtsstudierende liegen. Um besser abschätzen zu können, mit welchen Voraussetzungen affektiv-emotionaler Art bei einer breiteren Implementierung im Lehramtsstudium gerechnet werden kann, wurden N = 938 Lehramtsstudierende im Masterstudium an der Universität Paderborn zu ihren Emotionen und Bereitschaften zur Arbeit mit Eigenvideografien befragt. Dabei wurde auch erfasst, wie sich diese je nach bestehenden Erfahrungen zur Arbeit mit Videografien unterscheiden. In den Ergebnissen zeigen sich kaum affektiv-emotionale Reaktionen zur Eigenvideografie, und wenn, vor allem Gefühle der Unsicherheit. Zu beachten ist, dass zwar bei gut der Hälfte der Studierenden eine eher hohe generelle Bereitschaft zur Eigenvideografie besteht, eine konkrete Intention bzw. eine konkrete Volition zur Videografie aber geringer ist. Die ca. 10 % der Studierenden mit Eigenvideografieerfahrung im Studium zeigen erwartungsgemäß höhere Bereitschaften, aber unerwartet keine signifikant positiveren Emotionen. Insgesamt verdeutlichen die Ergebnisse, dass bzgl. der Akzeptanz der Studierenden ein höheres Potenzial zur Implementation von Eigenvideografien im Studium vorliegt, als aktuell ausgeschöpft wird.
Keywords: Lehrerbildung; Videografie; Praxissemester; Emotionen; Akzeptanz

In der freiheit musicirt: Musikpraxis und -erziehung in den Taschenkalendern Kaspars von Fürstenberg - Lauert, Markus (Musiklandschaften zwischen Pader und Rhein. Verflechtung und Pluralisierung entlang des Hellwegs)

Nanosecond gating of superconducting nanowire single-photon detectors using cryogenic bias circuitry - Hummel, Thomas; Widhalm, Alex; Höpker, Jan Philipp; Jöns, Klaus; Chang, Jin; Fognini, Andreas; Steinhauer, Stephan; Zwiller, Val; Zrenner, Artur; Bartley, Tim (Optics Express)
Superconducting nanowire single-photon detectors (SNSPDs) show near unity efficiency, low dark count rate, and short recovery time. Combining these characteristics with temporal control of SNSPDs broadens their applications as in active de-latching for higher dynamic range counting or temporal filtering for pump-probe spectroscopy or LiDAR. To that end, we demonstrate active gating of an SNSPD with a minimum off-to-on rise time of 2.4 ns and a total gate length of 5.0 ns. We show how the rise time depends on the inductance of the detector in combination with the control electronics. The gate window is demonstrated to be fully and freely, electrically tunable up to 500 ns at a repetition rate of 1.0 MHz, as well as ungated, free-running operation. Control electronics to generate the gating are mounted on the 2.3 K stage of a closed-cycle sorption cryostat, while the detector is operated on the cold stage at 0.8 K. We show that the efficiency and timing jitter of the detector is not altered during the on-time of the gating window. We exploit gated operation to demonstrate a method to increase in the photon counting dynamic range by a factor 11.2, as well as temporal filtering of a strong pump in an emulated pump-probe experiment.
Keywords: Atomic and Molecular Physics; and Optics

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study. - Stutz, Bianca; Buyken, Anette E.; Schadow, Alena; Jankovic, N; Alexy, U; Krueger, Betina (Appetite)

Location-Based Service and Location-Contextualizing Service: Conceptualizing the Co-creation of Value with Location Information - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Proceedings of the 56th Conference on System Sciences)

Mechanically Joined Extrusion Profiles for Battery Trays - Neumann, Stefan; Meschut, Gerson; Otroshi, Mortaza; Kneuper, Florian; Schulze, Andre; Tekkaya, Erman

Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Practice-Oriented Research in Tertiary Mathematics Education

Examples of AI-based Assistance Systems in context of Model-Based Systems Engineering - Schrader, Elena; Bernijazov, Ruslan; Foullois, Marc; Hillebrand, Michael; Kaiser, Lydia; Dumitrescu, Roman (2022 IEEE International Symposium on Systems Engineering (ISSE))

Are Neural Bug Detectors Comparable to Software Developers on Variable Misuse Bugs? - Richter, Cedric; Haltermann, Jan Frederik; Jakobs, Marie-Christine; Pauck, Felix; Schott, Stefan; Wehrheim, Heike (37th IEEE/ACM International Conference on Automated Software Engineering)

Benchmark Fuzzing for Android Taint Analyses - Schott, Stefan; Pauck, Felix (2022 IEEE 22nd International Working Conference on Source Code Analysis and Manipulation (SCAM))

Scaling Arbitrary Android App Analyses - Pauck, Felix (37th IEEE/ACM International Conference on Automated Software Engineering)

Does Augmented Reality Help to Understand Chemical Phenomena during Hands-On Experiments?–Implications for Cognitive Load and Learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“ - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Experimentelle und modellbasierte Untersuchungen zum Prozessverhalten von teilkristallinen Materialien im Spritzgießsonderverfahren GITBlow - Kröker, Michael

Experimentelle Kompetenz Physikstudierender - Bauer, Anna Brigitte
Für den Erwerb fachmethodischer Fähigkeiten stellen Laborpraktika eine zentrale Lerngelegenheiten des Physikstudiums dar. Trotz ihrer hohen Bedeutung fehlt ein hochschulfachdidaktischer Diskurs zu einer lehr-lerntheoretischen Fundierung. Zudem wird ihre Lernwirksamkeit aufgrund der bestehenden didaktischen Gestaltung kritisiert. Die weit verbreiteten engmaschigen Aufgabenstellungen enthalten keine Anreize zur tiefergehenden Auseinandersetzung mit den Inhalten. Um der Diskrepanz zwischen den Zielsetzungen und den von den Lernenden erworbenen Fähigkeiten entgegenzuwirken, liegen aktuell nur wenige und zudem nur punktuelle Grundlagen für eine evidenzbasierte Überarbeitung dieses Veranstaltungsformates vor. Ziel dieser Arbeit ist daher, einen Vorschlag für ein performanzorientiertes Kompetenzstrukturmodell auf universitärem Niveau zu entwickeln, das die Inhaltsbereiche, die experimentellen Fähigkeiten und Fertigkeiten sowie die Qualitätsausprägungen experimenteller Handlungen systematisiert.Die Modellierung ist auf Basis der Analyse videografierter experimenteller Performanz von 16 unterschiedlich fähigen Proband:innen realisiert worden. Für die Entwicklung der Dimensionen Fachmethodik und Qualitätsausprägung werden unter Nutzung der qualitativen Forschungsansätze Dokumentarische Methode und Typenbildung die charakteristischen Merkmale universitären Experimentierens identifiziert und anschließend systematisiert. Zur Prüfung der Passung des Modells zur Perspektive der Wissenschaft Physik ist ein Interrating mit einem Fachwissenschaftler durchgeführt worden, das sehr gute Übereinstimmungswerte liefert. Die Passung des Modells zur Perspektive der Praktikumsleiter:innen ist durch ein Expertenrating erfolgt. Ein Rangfolgen-Vergleich zeigt hohe Übereinstimmungswerte.

Supporting Business Model Decision-making in B2B Ecosystems: A Framework for Using System Dynamics - Ksouri-Gerwien, C.; Vorbohle, Christian (Proceedings of the 55th Hawaii International Conference on System Sciences (HICSS))

Literaturen vom 19. bis zum 21. Jahrhundert (thematische, ästhetische, mediale Transformationen hin zu einer technologisch aufgerüsteten Weltkommunikation) - Öhlschläger, Claudia (Grundthemen der Literaturwissenschaft: Weltliteratur.)

Rezension: Chiara Conterno / Astrid Dröse: Deutsch-italienischer Kulturtransfer im 18. Jahrhundert. Konstellationen, Medien, Kontexte - Süwolto, Leonie (DAJ)